PSYCHOLOGICAL TRAINING OF A SOLDIER IN THE SYSTEM OF A MILITARY LEADER'S PEDAGOGICAL ACTIVITY - Kucheriavyi, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
Every officer, sergeant, military trainer or other person, who meets the requirements and criteria of the military leadership, has a direct influence on forming different components of soldier's readiness for professional activity. The issue of psychological training of military servicemen during pedagogical activity of a military leader is studied in the article as an actual direction of this forming process. In particular two tasks are completed. Firstly, the soldier's features that predetermine formation of their psychological readiness for service are revealed. Secondly, the ways of forming those features are determined for teaching and educational events conducted by a military leader. Generalized definition of the term of soldier's psychological readiness for professional activity is given on the base of analysis of scientific literature. This research step has let to specify the complex of soldier's characteristics as directions of psychological training. The set of internal resources of a soldier for performing professional duties in combat situations is relegated to these characteristics. It is about professional orientation values (professional knowledge and skills, views, believes and principals of service duty obeying), motivation, emotional intelligence and stress resistance, strong-willed qualities, psychological knowledge and skills of a military serviceman. Each of these internal resources as well as the ways to form ones in the system of military leader's pedagogical activity are detailed in the research. Active methods of practice training, creating situations of analyzing and estimating of military reality by a soldier, who says personal attitude to it, individual and group dialogues, using actions for making stressful situations and emotional exhibiting by military servicemen, their physical exhaustion are distinguished among such ways. Herewith the specifics of particular soldier's internal resources and peculiarities of their formation are taken into account. From among these features it is accentuated that only complex work of all military leaders (trainers, commanders, officer-psychologists etc.) does guarantee complete theoretical and practical psychological readiness of soldiers.
Keywords: military leader, soldier, psychological training, psychological readiness, internal resources, pedagogical activity, training and educational events